HAKIKAT PENILAIAN DALAM PENDIDIKAN SENI: MENAFSIRKAN HASIL PENGUKURAN UNTUK MENILAI KUALITAS PEMBELAJARAN - Kingkin Prasetyo Wati; Hartono; Udi Utomo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Authentic assessment is an evaluation approach designed to measure students' competencies comprehensively and contextually in arts and culture learning. This study aims to examine the implementation of authentic assessment, measurement results, and its effectiveness in improving motivation and quality of arts and culture learning at the elementary and secondary school levels. The research method used a literature study with techniques of reviewing various sources such as books, journals, articles, and previous research results relevant to the field of arts and culture and the Merdeka Curriculum. Data analysis was carried out descriptively by organizing and presenting the results of the literature review systematically to obtain comprehensive findings regarding the process and results of authentic assessment. The results of the study show that authentic assessment not only assesses artistic works but also the creative process and reflective attitudes of students, thereby supporting more interactive and meaningful learning. In addition, authentic assessment has a positive impact on increasing learning motivation and the development of students' multidimensional competencies. This study recommends teacher training and the development of assessment instruments as strategies to strengthen the implementation of authentic assessment in the field of arts and culture. Thus, authentic assessment plays an important role in improving the quality of arts education through a holistic and sustainable approach.